As gravuras rupestres do Monte Faro (Valença, Viana do Castelo) – Um exemplo maior das Arte Atlântica peninsular - Alves, Lara Bacelar; Reis, Mário (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
On the northern fringes of Serra do Extremo, overlooking the valley of the river Minho, the hills of Monte Faro and Monte dos Fortes revealed an exceptional collection of prehistoric rock carvings belonging to the Iberian Atlantic Art tradition. In the late 1970s and early 1980s, A. Leite da Cunha e E. J. Silva studied here the well-known sites of Monte da Laje, Tapada do Ozão e Monte dos Fortes. Between 2013 and 2015, a new research project amplified he numbers to over one hundred carved rocks, amongst which 91 are dated to Late Prehistory. This allows us to acknowledge that this is the largest assemblage of Atlantic Art identified, so far, in Portugal. This paper, which inaugurates the dissemination of the research outcomes, reveals how the project was structured, the methodology adopted and offers a preliminary description of the archaeological sites.